The Implementation of Students Placement in Majors at the Senior High School 4 South Bengkulu - Anisa Sari Riski Sofian; Indra Ibrahim (Universitas Negeri Padang, 2019)
Through placement and channeling services the guidance and counseling teacher seeks to help one or more individuals to independently be able to dig up, determine and develop potential, interests, talents, attitudes and goals based on current values, so some students can plan or determine what majors are appropriate for them. This method of study is descriptive research that aims to describe any data that is available for student placement services at the senior high school 4 south Bengkulu. The data collection techniques use the angkets, by alternate answers to use Likert scale. Overall research results include all of the indicators for variable service placement and distribution to majors or study programs in the category resulting in a percentage of 70,8%. The results of the study are that guidance and counseling teacher could continue to practice more advanced student placement in accordance with the student’s potential. The students can increase their knowledge of work by working together with guidance and counseling teacher, so students don’t have a very poor understanding of majors.